Soil Characterization: An Indicator of Soil Pollution and Base for Soil Restoration: Soil Characterization: An Indicator of Soil Pollution and Base for Soil Restoration - Wahid, Fazal; Alrawi, Luqman I.; Rahim, Muhammad; Zulqarnain; Riaz, Salman; Jamal, Arshad; Alla Ud Din; Khan, Nadir (International Journal of Economic and Environmental Geology, 2019)
Soil is considered as the major source of nutrients for plants and micro-organisms. It acts as a sink for the deposition of minerals and metal ions from weathering and anthropogenic activities. Some of these metal ions and minerals are beneficial for the plants and their dependents, while some of the metal ions and minerals are extremely toxic in higher concentrations. Therefore, the soil characterization as a source for the detection of metal ions in the soil of disturbed and un-disturbed areas of Peshawar was considered for the present study. Soil samples were collected randomly and digested for the extraction of metal ions. Higher concentration of metal ions was observed in soil samples of disturbed sites as compared to undisturbed. The results indicated that human activities are the main cause of soil pollution. It was recommended that environmental protection and urban development agencies should focus before these toxics adversely affect the local population.